Income tax on PGBL and VGBL pension plans: Analysis of progressive and regressive forms of taxation - Leal Martins, Fábio Garrido (2021)
AbstractPurpose – The study investigates incentives in two types of private pension plans in Brazil: PGBL and VGBL. It identifies which one to choose to minimize income tax, considering both progressive and regressive forms of taxation. Theoretical framework – Based on Sutcliffe (2016), the individual decision-making process depends on the taxonomy of tax incentives (Disney & Whitehouse, 1999) and economic effects (Barr & Diamond, 2009; Armstrong, Davis, & Ebell, 2015). Design/methodology/approach – This study used an innovative approach, calculating the actuarial present value gross and net of tax for nominal cash flows, applied to the objective function that minimizes the average effective income tax rate – according to the definition by Fullerton (1984). A simulator was created for the optimal decision of representative individuals regarding the form of taxation to choose, thus reducing the amount of tax payable. Research Practical & Social implications – We advise those with PGBL and VGBL pension plans on the best decision regarding forms of taxation, thus contributing to an improvement in tax legislation. Originality/value – The study’s main contribution lies in calculating actuarial annuity gross and net of income tax, impacted by inflation over time, in addition to calculating traditional variables such as real interest rate, taxable income, deductible expenses, age, sex, and the life table. Keywords – private pension plans, PGBL, VGBL, tax relief, income tax.